Persepsi masyarakat terhadap pengobatan tradisional pada penyakit tulang - Sri Wahyuni; Cut Fitriani Rahayu; Cut Dini Shaleha; Rahmat Riski; Najwa Salsabila; Sayyed Sabiq; Syakila Zaura (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Traditional medicine is still widely used by rural communities as an alternative approach to managing bone diseases and musculoskeletal complaints. The practice of bone sorting in Samuti Village by local practitioners remains trusted and used by the community due to cultural factors, accessibility, and perceived empirical experience. Purpose: To analyze community perceptions and levels of trust toward traditional treatment for bone diseases in Samuti Village. Method: The study used a descriptive qualitative approach, collecting data through in-depth interviews and participant observation with community members who had undergone bone-sharpening treatment. Data were analyzed thematically to describe perceptions, experiences, and factors influencing their choice of traditional medicine. Result: The majority of people have a positive perception of traditional medicine. Bone massage is considered effective for treating mild to moderate ailments such as sprains, aches, and joint pain. Ease of access, an